Intelligent Web Based System For Diagnosing Digestive Canser System - Marliza, Abdul Malik (2002)

(untitled)
Cancer is one of the dangerous diseases which can contribute to a high death rate among the patients. This is due to failures to detect the symptoms of the disease as early as possible. This project proposed a prototype which function is to help the users to perform early diagnosis in a similar way of an expert. Human's digestion system has been chosen as a domain for the developed prototype. The system comprises of six parts, namely as stomach, colon, liver, bladder, pancreatic and esophagus. Digest-Ex has a capability to detect symptoms of cancer in any of these parts through a series of question and answer session. Apart from performing early cancer diagnosis, Digest-Ex also provides the users with general information on human's digestion system as well as specific information on each type of digestive system cancer and their treatment procedures. As a web based system, the prototype can be accessed through Internet by everybody at anytime, regardless of wherever he or she is.